2023
DOI: 10.1002/lpor.202300244
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Frequency Manipulation of a Quartz Crystal for Phase‐Matched Second‐Harmonic Vacuum Ultraviolet Generation

Abstract: Second harmonic generation (SHG) is the nonlinear response of electrons to high‐intensity light and has been successfully applied in basic scientific research and modern optoelectronics. However, constrained by stringent but essential phase‐matching conditions, efficient vacuum ultraviolet (VUV) SHG is still a challenge in solid‐state lasers. Here, this work employs a spatial frequency manipulation strategy to realize artificially structured phase‐matching conditions in ordinary quartz crystals for efficient f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The output wavelength covered 221 to 332 nm, and the conversion efficiency at the peak power was more than 1%. Very recently, they developed a metacrystal of quartz and increased the emission conversion efficiency at 177.3/167.8 nm to 0.23%, which is close to that with RBBF [88]. Yuan et al demonstrated a QPM structure inside a Type II waveguide in LiNbO 3 crystal (Figure 3g); the normalized conversion efficiency was enhanced to 8.76% W −1 cm −2 [89].…”
Section: χ (2) -Erasing Technique Using Femtosecond Lasermentioning
confidence: 73%
“…The output wavelength covered 221 to 332 nm, and the conversion efficiency at the peak power was more than 1%. Very recently, they developed a metacrystal of quartz and increased the emission conversion efficiency at 177.3/167.8 nm to 0.23%, which is close to that with RBBF [88]. Yuan et al demonstrated a QPM structure inside a Type II waveguide in LiNbO 3 crystal (Figure 3g); the normalized conversion efficiency was enhanced to 8.76% W −1 cm −2 [89].…”
Section: χ (2) -Erasing Technique Using Femtosecond Lasermentioning
confidence: 73%